Side Effects Profile among Healthcare Workers after the Administration of Activated mRNA-1273 as a Booster Following 2 Shots of Inactivated (CoronaVac) Vaccine - Maryani, Nova; Permana, Iman; Setyonugroho, Winny; Ulfa , Maria; Fakhriani, Rizka; Sutantri, - (Bangladesh Journal of Medical Science, 2022)
Objective: This study focuses on investigating the profile of all side effects of the mRNA-1273 vaccine for healthcare workers. Material and method: A cross-sectional design were used to explore the side effects of the mRNA-1273 vaccine for healthcare workers in Yogyakarta and Central Java, Indonesia. The survey was conducted through Google form after 119 healthcare workers in Yogyakarta and Central Java receiving the mRNA-1273 vaccination as a booster in May-August 2021. Results and discussion:The major goal of this research is to investigate the side effects of using the mRNA-1273 vaccine as a booster among healthcare workers in Yogyakarta and Central Java, Indonesia.Most (99.2%) of respondents admitted to feeling pain at the injection site, 42% the respondents also admitted to feeling swelling at the injection site as a moderate side effect, and 3.4% respondents reported vomiting as a rare side effect.This study found the low negative correlation between headache with p value 0.004 (p<0.05, r= -314) and nauseous with p value 0.012 (p<0.05, r= -300) towards the gender. We also found the low negative correlation between muscle aches with p value 0.033 (p<0.05) towards the ages (r= -257). Conclusion: The most common side effect after receiving the mRNA-1273 vaccine as a booster is a pain in the injection area. Female most frequent felt the headache and nauseous than man after received booster vaccination. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 801-807